Short-duration accretion states of Polars as seen in TESS and ZTF data - Duffy C; Ramsay G; Wu K; Mason PA; Hakala P; Steeghs D; Wood MA (OXFORD UNIV PRESS, 2025)
Polars are highly magnetic cataclysmic variables which have been long observed to have both high and low brightness states. The duration of these states has been previously seen to vary from a number of days up to years. Despite this, these states and their physical origin have not been explained in a consistent manner. We present observations of the shortest duration states of a number of Polars observed by ZTF and TESS. This has allowed us to determine that short-duration states are a relatively common feature across the population of Polars. Furthermore, we have been able to generalize the model of star-spot migration to explain both short-lived high and low states in Polars by incorporating the interaction between the magnetic field of the white dwarf and that of the star spots.